2018
DOI: 10.1371/journal.pone.0202591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH and feeding system on black soldier fly (Hermetia illucens, L; Diptera: Stratiomyidae) larval development

Abstract: Black soldier fly (BSF) is a generalist species able to reduce large quantities of organic substrates and is thus considered as an interesting solution for waste management. Moreover, as BSF larvae accumulate high quantities of nutrients during their growth, they are valued because of their potential to produce products such as protein meal or fat for livestock feeds. Abiotic factors can influence larva growth, and a more detailed knowledge and control of these parameters can lead to the development of mass BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 51 publications
3
78
0
4
Order By: Relevance
“…Under more natural conditions, black soldier fly larvae occur at high larval numbers in dung piles ( Sheppard 1983 , Fatchurochim et al 1989 ) or carrion ( Tomberlin et al 2005 ), which are normally associated with unpredictable pathogen levels ( Diclaro and Kaufman 2009 ). The ability of black soldier fly larvae to modify pH ( Ma et al 2018 , Meneguz et al 2018a ) can result in suppressed pathogens ( Wang et al 2015 ) and improve the palatability of the food ( Deshpande et al 2015 ). Furthermore, black soldier fly larvae produce antimicrobial peptides that can inhibit a broad spectrum of bacteria ( Park et al 2014 , 2015 ; Vogel et al 2018 ), and studies have shown that black soldier fly larvae can reduce Escherichia coli ( Erickson et al 2004 , Liu et al 2008 ), Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Under more natural conditions, black soldier fly larvae occur at high larval numbers in dung piles ( Sheppard 1983 , Fatchurochim et al 1989 ) or carrion ( Tomberlin et al 2005 ), which are normally associated with unpredictable pathogen levels ( Diclaro and Kaufman 2009 ). The ability of black soldier fly larvae to modify pH ( Ma et al 2018 , Meneguz et al 2018a ) can result in suppressed pathogens ( Wang et al 2015 ) and improve the palatability of the food ( Deshpande et al 2015 ). Furthermore, black soldier fly larvae produce antimicrobial peptides that can inhibit a broad spectrum of bacteria ( Park et al 2014 , 2015 ; Vogel et al 2018 ), and studies have shown that black soldier fly larvae can reduce Escherichia coli ( Erickson et al 2004 , Liu et al 2008 ), Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The function r assim max represents the ingestion/feeding potential of the larvae in relation to it its current size and the maximum size it can reach when infinitely fed. With this Eq (17), a relation between the development sum and the size dependent ingestion is established. Maturation stage.…”
Section: Plos Onementioning
confidence: 99%
“…Finally, the regulation function for development rate r dev can be modelled similarly to Eq (17), a function of all factors affecting development, as…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, this species has been used in different studies for waste bioconversion . Indeed, BSF larvae are extremely voracious as well as highly suitable for being fed different organic wet substrates (with wide pH and moisture ranges), including by‐products originating from the food industry, agricultural and livestock processes, municipal garden waste, and household food scraps …”
Section: Introductionmentioning
confidence: 99%